2003
DOI: 10.1053/jlts.2003.50164
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of liver transplantation for patients infected by hepatitis C, including those infected by genotype 4

Abstract: Predictors of hepatitis C virus (HCV)-related liver disease posttransplantation are still unclear. The impact of HCV genotype on outcome of transplantation has been studied, but conclusions are not in agreement. The role of HCV genotype 4 on the result of liver transplantation requires further study. The aim of this study is to examine the outcome of liver transplantation for patients with HCV genotype-4 infection. The study group included 128 patients who underwent transplantation for HCV infection: 28 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 43 publications
(56 reference statements)
2
37
3
1
Order By: Relevance
“…The rate of fibrosis progression in our study is also lower than that reported by Firpi et al and Wali et al (39,40). This observed difference may be accounted for by the different scoring system used in these two studies, and, the fact that Wali et al analyzed liver biopsies performed at a median of 1.92 (range 0.24-11.48) years after liver transplantation rather than at a discreet time point as in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…The rate of fibrosis progression in our study is also lower than that reported by Firpi et al and Wali et al (39,40). This observed difference may be accounted for by the different scoring system used in these two studies, and, the fact that Wali et al analyzed liver biopsies performed at a median of 1.92 (range 0.24-11.48) years after liver transplantation rather than at a discreet time point as in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…On the other hand, studies with African and Middle Eastern populations suggest a frequent association with cirrhosis and a rapid fibrosis progression rate following liver transplantation (5,7). Although this genotype was previously categorized as difficult to treat, our results are in accordance with the more recent trials that suggest a response intermediate between those of genotype 1 and non-1 genotypes.…”
supporting
confidence: 91%
“…These factors included the development of new immunosuppressive agents, a philosophy in which less global immunosuppression was used in patients with recurrent HCV, the increased use of interferon therapy in patients before undergoing transplantation, and the use of donor organs from patients with advanced age and unstable hemodynamics. [48][49][50][51][52] Each of these factors in and of itself could have altered the natural history of recurrent HCV infection. These and other potentially important factors are listed in Table 2.…”
Section: Factors Associated With Fibrosis Progressionmentioning
confidence: 99%